MOTIVASI SISWA DALAM MEMANFAATKAN LAYANAN BIMBINGAN DAN KONSELING - Saidah Tunnoor (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2017)
The purpose of the study is to obtain a description of what can motivate in utilizing guidance and counseling services in MAN 1 Banjarmasin. The data digging tool used is questionnaire and interview as a complement. Analysis of data in use is the formula percentage. From the results of data processing shows a small part (36,886%) students who expressed always take advantage of guidance and counseling services on impulse ability, want to know, understand, apply in daily life and get parent support, education facilities, guidance from teacher BK (konselor), Support from friends, media counseling guidance services on the internet. A small portion (32.148%) of students stated freqently. A small number (24.890%) of students stated rarely. The smallest part (6,074%) of students stated never. Finally based on the results of research can be concluded that a small part of the motivation of students in utilizing gudance and counseling services. Therefore it is necessary for the understanding and application of information about counseling guidance services in schools, so that between BP students and teachers or principals can work together well and responsibly